Effect of acidic and alkaline treatments to methylene blue adsorption from aqueous solution by coconut shell activated carbon - Nor Hakimin, Abdullah; Izzaty, Inu; Mohammad Khairul Azhar, Abdul Razab; An'amt, Mohamed Noor; Nurul Akmar, Che Zaudin; Mohd Sukhairi, Mat Rasat; Mohamad Faiz, Mohd Amin; Wan Nazwanie, Wan Abdullah; Nurasmat, Mohd Shukri; Zamani, A. H. (Unique Research Publishers, 2018)
In recent years, pollution from dye wastewater becomes a serious environmental problem due to the high demand and the increment of dye application in textile industry. The purpose of this study was to investigate the potential application of coconut shell activated carbon as methylene blue (MB) removal from aqueous solution. The carbonization process was conducted in temperature range from 300 to 500 °C. For the activation process, two different activating agents namely phosphoric acid, H3PO4 (acid activating agent) and sodium hydroxide, NaOH (basic activating agent) were used. Physical characterization of coconut shell activated carbon (CSAC) was realized by using X-ray diffraction (XRD) for phase identification. After that, the percentage of dye removal was investigated in order to determine the adsorption capacity of the prepared activated carbon. It can be concluded that when the dosage of CSAC increased, the amount of dye removal would also be increased. The results indicated that the coconut shell activated carbon could be employed as a low cost alternative in controlling wide range of sorption processes.